2014
DOI: 10.1292/jvms.14-0223
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor Effects of Acetylcholine, Bradykinin, Noradrenaline, 5-Hydroxytryptamine, Histamine and Angiotensin II on the Mouse Basilar Artery

Abstract: We investigated the responsiveness of the mouse basilar artery to acetylcholine (ACh), bradykinin (BK), noradrenaline (NA), 5-hydroxytryptamine (5-HT), histamine (His) and angiotensin (Ang) II in order to characterize the related receptor subtypes in vitro. ACh and BK induced endothelium-dependent relaxation of precontracted arteries with U-46619 (a thromboxane A2 analogue). Atropine (a non-selective muscarinic receptor antagonist) and Nω-nitro-L-arginine (a NO synthase inhibitor, L-NNA) shifted the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
(32 reference statements)
3
7
0
Order By: Relevance
“…We have previously reported that vasodilation induced by acetylcholine, which is dependent on NO production from endothelial cells, was decreased in a basilar artery isolated from MeHg-exposed mice [14, 15]. In this study, we showed that treatment of 0.3 µ M MeHg significantly inhibited NO production, but not expression of eNOS, in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 50%
“…We have previously reported that vasodilation induced by acetylcholine, which is dependent on NO production from endothelial cells, was decreased in a basilar artery isolated from MeHg-exposed mice [14, 15]. In this study, we showed that treatment of 0.3 µ M MeHg significantly inhibited NO production, but not expression of eNOS, in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 50%
“…This has been attributed to the relative expression of 5‐HT receptor subtypes in different tissues and species (Watts et al, 2012). In mice, the species under consideration in the present study, 5‐HT has been reported to have a contractile effect on isolated arteries (Islam et al, 2014; Matsumoto, Kobayashi, Ishida, Taguchi, & Kamata, 2010; McKune & Watts, 2001). The in vivo vascular response to 5‐HT, on the other hand, is typically vasodilation, reflecting an interplay between its direct vascular actions and its involvement in the neural regulation of cardiovascular function (Watts et al, 2012).…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, in addition to the increase in expression of tryptase, the increase in 5-HT and HA also occurs during acupoint sensitization. As neurotransmitters and immune mediators, 5-HT and HA are important regulators of the microcirculatory system [ 37 38 ] and involved in allergy [ 39 40 ]. These factors, 5-HT and HA, have been attributed a potential role in the exchange of information between MCs and nerve terminals [ 41 ].…”
Section: Discussionmentioning
confidence: 99%